9th World Congress on Itch report. Issue 2 (June 2018) - Sanders, Kristen M.; Nattkemper, Leigh A.
Abstract : The 9th World Congress on Itch, the biennial meeting of the International Forum for the Study of Itch, was held on October 15–17, 2017, in Wroclaw, Poland. The meeting was hosted by Jacek C. Szepietowski and attended by 303 basic researchers, clinicians, and others interested in the science and treatment of itch, making it the best-attended World Congress on Itch yet. Over the 3 days of the conference, there were 86 oral presentations and 80 posters. The meeting program, abstracts, and other information about the congress are available athttp://itch2017.syskonf.pl/ .